Mediating Factors Influencing the Adoption of Green Technology by SMEs for Sustainable Performance: A Systematic Literature Review - Sobar, Agus (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This research aims to elucidate the background and theoretical framework underlying the adoption of green technology by MSMEs to achieve sustainable performance. This study employs the PRISMA systematic review methodology to analyze 40 empirical publications regarding the mediating factors influencing green technology adoption by MSMEs in achieving sustainable performance, spanning from 2017 to 2024 and encompassing diverse nations. A concise summary and recommendations for future research goals are provided for each applicable theory. This study indicates that, despite extensive prior research, the majority of studies examine sustainable performance through factors that mediate the adoption of green technologies. Additionally, the employed theories include the Resource-Based View (RBV), Technology Acceptance Model (TAM), Innovation Theory, and Sustainability Theory. This research aids policymakers in formulating policies and incentives that promote the use of green technology by MSMEs. For MSMEs, these findings offer pragmatic direction on enhancing green innovation capabilities and leveraging green technology to attain sustainable performance.